1993
DOI: 10.1002/pca.2800040508
|View full text |Cite
|
Sign up to set email alerts
|

Off‐line supercritical fluid extraction—high resolution gas chromatography applied to the study of moraceae species

Abstract: Supercritical fluid extraction with COz, performed in a home-made system, of rhizomes of Dorstenia bryoniifolia Mart. ex Miq. (Moraceae) and of bark roots of Brosimum gaudichaudii Trecul (Moraceae) afforded crude extracts that were analysed by high resolution gas chromatography (HRGC). The D. bryoniifolia extract contained, besides the previously reported pimpinelin and isohergapten, the furocoumarins psoralen, bergapten, isopimpinelin and the triterpenes a-and 9-amyrin and the acetate of the latter. The B . g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

1994
1994
1999
1999

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 8 publications
0
19
0
Order By: Relevance
“…The identification of the furocoumarins in the plants was performed by comparison of their retention time with those of authentic samples by co-injection of authentic standards and by their matching with the NIST 62500 data bank (with 62235 compounds) and also by their MS fragmentation pattern compared to the literature [2][3][4][5][6]16]. Mass spectral analysis indicated the absence of co-eluted compounds in the peaks ofpsoralen, bergapten, pimpinellin and isopimpineliln, under the chromatographic conditions employed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The identification of the furocoumarins in the plants was performed by comparison of their retention time with those of authentic samples by co-injection of authentic standards and by their matching with the NIST 62500 data bank (with 62235 compounds) and also by their MS fragmentation pattern compared to the literature [2][3][4][5][6]16]. Mass spectral analysis indicated the absence of co-eluted compounds in the peaks ofpsoralen, bergapten, pimpinellin and isopimpineliln, under the chromatographic conditions employed.…”
Section: Resultsmentioning
confidence: 99%
“…Most of them are known as "carapi/t" or "figueirilha". Some of them are used in folk medicines, mainly for skin diseases and as antiophidics [2][3]. Dorstenia species are known for their ability to synthesize linear and angular furocoumarins (psoralen, bergapten, pimpinellin and isopimpinellin) [2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Further to the preliminar report of some of the data herein presented 16 , a paper concerning the analysis of triterpenes from Brazilian Polypodiaceae was published, but with the aid of preparative purification steps and chemical transformations, for obtention of reference samples of some triterpenes not found commercially 17 .…”
Section: Discussionmentioning
confidence: 99%
“…Figure 2 shows a typical chromatographic profile from dechlorophyllated crude Dorstenia extracts. The extracts obtained from the leaves require a clean-up procedure for removal of the chlorophylls (filtration over active charcoal, described in Experimental), while the crude extracts obtained from the rhizomes could be directly analyzed by HRGC-MS. ln a previous work we have shown that SFE-CO2 (supercritical fluid extraction using CO2) also furnishes rhizome extracts suitable for direct analysis 15 .…”
Section: Identification Of the Compoundsmentioning
confidence: 99%
“…It has been experimentally proven that supercritical C0 2 can be an efficient alternative solvent over the conventional organic liquid solvents for many cases of selective extraction of bioactive substances from natural plants (1)(2)(3)(4). The supercritical fluid extraction (SFE) is more economical than liquid solvent extraction (5)(6)(7)(8).…”
mentioning
confidence: 99%